Evaluasi Pengungkapan Laporan Keuangan Daerah di Situs Internet: Studi pada Pemerintah Daerah Indonesia - Gatot Soepriyanto; Restya Aristiant (Binus Business Review, 2011)
The purpose of this study was to determine the extent of financial statement disclosure displayed on the website of local government in the years 2009-2010. The research method used is bibliography study and field study through the Internet. We found 2 types of financial information presented in the website, namely the information of financial statements and other financial information. There are 57 local governments that provide financial information from 392 local governments’ website. The 57 local government web sites, only nine local governments that provide information on its financial statements in accordance to SAP (Government Accounting Standards), while 40 local governments provide information on local government budgets (APBD) and 8 present the financial information other than financial statements according to SAP and budget information (APBD). These findings suggest that transparency and accountability of local governments related to the financial statements and other financial information on the website is still lacking.